Mechanical Characteristics of the Main Tower of a Polygonal Line Tower Cable-Stayed Bridge - Yan-feng Li; Ying He; Long-sheng Bao (Advances in Civil Engineering)
The main tower of a polygonal line tower cable-stayed bridge bears most of the axial force transmitted by the stay cable and also bears the moment under certain unbalanced load. For a polygonal line tower cable-stayed bridge, the main tower has a bending corner and the direction of huge axial force transmission changes at this bending corner where the axis of the main tower changes. This study examined a cable-stayed bridge with a single cable plane in Shenyang and used model test and finite element numerical comparative analysis to analyze the mechanical properties of the key parts, including the main tower bending corner of the concrete polygonal line tower. The results show a serious stress concentration phenomenon at the bending corner of the main tower but a small range of high stress area. After the stiffening plate is set at the corner, the stress concentration coefficient of the bending corner section decreases and the stiffening plate eliminates the out-of-plane bending phenomenon of the tower wall at the middle span side as vertical tensile stress occurs in the stiffener at the bending corner. Based on these results, the design should be improved to increase the angle of the stiffening plate corner and appropriately strengthen the configuration of the vertical main tensile steel bar and the surface anticracking steel mesh inside the stiffening plate.